Foucault's Disciplinary Society and Gender Dynamics: A Critical Appraisal - Aryal, Vijay (Journal of Political Science, 2025)
This paper assesses Michel Foucault's idea of a disciplinary society and its connection with gender dynamics. Foucault's contributions to different fields of knowledge, with philosophy, sociology, and gender studies, are emphasized and his major publications, such as "Discipline and Punish," "The History of Sexuality," and others, are discussed as per the significance. The context of Foucault's disciplinary society theory is explored, underlining its implications for understanding power relations and social control. Gender dynamics are presented as the social, cultural, and political characteristics inducing the structure, performance, and regulation of gender identities. The paper critically evaluates the intersection of Foucault's disciplinary society and gender dynamics, considering the strengths and limitations of his theories in focusing on power and gender associations. Methodology comprises a wide-ranging review of academic resources, analysing Foucault's work and other concerned works. Foucault's disciplinary society suggests the shift in power from sovereign to disciplinary, the practices of discipline, and the effects on individuals and institutions. The analysis reveals how disciplinary power functions in several societal spaces, such as classrooms, prisons, and health facilities, inducing gendered norms and expectations. Foucault's concepts are useful to explore power and gendered disciplinary practices, surveillance of gendered bodies, technologies of gender, and the potential for resistance and subversion. However, the paper also concedes limitations in Foucault's dealing of gender as a social construct, insufficiency of an intersectional perspective, and incomplete analysis of resistance strategies. In conclusion, Foucault's concept of a disciplinary society offers valuable visions into power dynamics and gender relations within societal structures. Combining his concepts with intersectional feminist perspectives can develop our understanding of power mechanisms and the complications of gender dynamics in modern societies.